2015
DOI: 10.3899/jrheum.150058
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Autoimmune Cytopenia to Glandular and Systemic Manifestations in Primary Sjögren Syndrome: Analysis of 113 Korean Patients

Abstract: Autoimmune cytopenia is closely associated with severe ocular surface damage in pSS. Therefore, assessment of xerophthalmia by ophthalmologists may be mandatory, particularly in patients with pSS with cytopenia, even if patients do not complain of eye dryness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
(16 reference statements)
1
5
0
Order By: Relevance
“…We observed that thrombocytopenia occurred in 22 (44.9%) patients, higher than 12.03%-23.9% reported by a few studies based on adult pSS patients (23)(24)(25), but similar to the 48.9% reported by Wu et al (26). However, published pediatric cohort studies focusing on thrombocytopenia secondary to pSS are lacking at present.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We observed that thrombocytopenia occurred in 22 (44.9%) patients, higher than 12.03%-23.9% reported by a few studies based on adult pSS patients (23)(24)(25), but similar to the 48.9% reported by Wu et al (26). However, published pediatric cohort studies focusing on thrombocytopenia secondary to pSS are lacking at present.…”
Section: Discussionsupporting
confidence: 74%
“…This suggests that pSS patients with thrombocytopenia may be less likely to experience exocrine gland involvement. Reportedly, ILD is negatively related to thrombocytopenia in pSS ( 23 , 24 , 26 ); however, due to the limited number of patients with ILD in our study, we analyzed the comparison of organ involvement, except that of hematology, and found that patients with thrombocytopenia were less likely to experience other organ involvement. Moreover, autoantibodies inducing complement-mediated destruction of platelets and inhibiting megakaryocyte function are reportedly involved in thrombocytopenia development ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 88%
“…According to previous studies, patients with Sjögren's syndrome are more susceptible to hematological abnormalities than general population. [10][11][12] these hematological abnormalities are known as autoimmune cytopenia, possibly related with the degree of extra-glandular or glandular organs involvement. [10][11][12] in this vulnerable population, certain antipsychotics use, especially risperidone, may further elevate the risk of leukopenia.…”
Section: Discussionmentioning
confidence: 99%
“…The cytopenias are the main cellular abnormalities, while hyper- and hypogammaglobulinemia, monoclonal gammopathy, cryoglobulinemia, and the presence of autoantibodies are the most frequent humoral manifestations [ 175 ]. Leukopenia was reported in 19% to 22% of pSS patients [ 176 ], while neutropenia and lymphopenia were noted in 14 to 27.3% [ 177 ] and in 14 to 23.9% of the pSS patients, respectively [ 116 , 178 , 179 ]. Secondary to chronic inflammation, anemia may occur in between 17.1 and 23.9% of patients [ 180 ], while thrombocytopenia was reported between 29.3 to 30.5% of pSS patients [ 181 , 182 ].…”
Section: Extraglandular Manifestationsmentioning
confidence: 99%